Paragenesis of multiple platinum-group mineral populations in Shetland ophiolite chromitite: 3D X-ray tomography and in situ Os isotopes. (1st November 2017) - Prichard, H.M.; Barnes, Stephen J.; Dale, C.W.; Godel, B.; Fisher, P.C.; Nowell, G.M.
Abstract: Chromitite from the Harold's Grave locality in the mantle section of the Shetland ophiolite complex is extremely enriched in Ru, Os and Ir, at µg/g concentrations. High-resolution X-ray computed tomography on micro-cores from these chromitites was used to determine the location, size, distribution and morphology of the platinum-group minerals (PGM). There are five generations of PGM in these chromitites. Small (average 5 µm in equivalent sphere diameter, ESD) euhedral laurites, often with Os-Ir alloys, are totally enclosed in the chromite and are likely to have formed first by direct crystallisation from the magma as the chromite crystallised. Also within the chromitite there are clusters of larger (50 µm ESD) aligned elongate crystals of Pt-, Rh-, Ir-, Os- and Ru-bearing PGM that have different orientations in different chromite crystals. These may have formed either by exsolution, or by preferential nucleation of PGMs in boundary layers around particular growing chromite grains. Thirdly there is a generation of large (100 µm ESD) composite Os-Ir-Ru-rich PGM that are all interstitial to the chromite grains and sometimes form in clusters. It is proposed that Os, Ir and Ru in this generation were concentrated in base metal sulfide droplets that were then re-dissolved into a later sulfide-undersaturated magma, leaving PGM interstitial to the chromite grains. Fourthly there is a group of almost spherical large (80 µm ESD) laurites, hosting minor Os-Ir-Ru-rich PGM that form on the edge or enclosed in chromite grains occurring in a sheet crosscutting a chromitite layer. These may be hosted in an annealed late syn- or post magmatic fracture. Finally a few of the PGM have been deformed in localised shear zones through the chromitites. The vast majority of the PGM – including small PGM enclosed within chromite, larger interstitial PGM and elongate aligned PGM – have Os isotope compositions that give Re-depletion model ages approximately equal to the age of the ophiolite at ∼492 Ma. A number of other PGM – not confined to a single textural group – fall to more or less radiogenic values, with four PGM giving anomalously unradiogenic Os corresponding to an older age of ∼1050 Ma. The 187 Os/ 188 Os isotopic ratios for PGM from Cliff and Quoys, from the same ophiolite section, are somewhat more radiogenic than those at Harold's Grave. This may be due to a distinct mantle source history or possibly the assimilation of radiogenic crustal Os.